Effective Communication Education for Families Against Neglect and Psychological Abuse of the Elderly - Dewi Utari; Ngatoiatu Rohmani (Universitas STRADA Indonesia, 2025)
Background: Older adults experience a progressive aging process that can impact their physical, psychological, social, and spiritual well-being. When these changes become severe, they may contribute to the development of illnesses or disorders. Although family plays a crucial role in supporting the elderly, inadequate communication and understanding often lead, intentionally or unintentionally, to mistreatment. Purpose: This study aimed to identify the differences between pre dan post health education on effective communication to the family so that neglect and psychological abuse can be prevented. Methods: This was a quasi-experimental study with pre-post-test one group design. A total of 39 family members and 39 elderly people in Sentolo Kulon Progo Yogyakarta were selected using simple random sampling. The research was conducted in 2023. The instrument was adopted from the previous study which was Elder Assessment Instrument (EAI) and data were analysed using Wilcoxon test. In addition, the health education program was conducted over approximately five weeks, consisting of four sessions with a one-week interval between each session. The educational content was delivered using a module-based approach. Results: The result showed that the p-value of Wilcoxon test was 0.000. It meant that there were differences between pre and post intervention on the level of elder neglect and psychological abuse. Conclusion: It can be concluded that health education on effective communication among families is able to reduce the rate of neglect.